Banking Crises and Central Bank Digital Currency in a Monetary Economy - Tarishi Matsuoka; Makoto Watanabe (CESifo GmbH, 2025)
This paper examines the role of Central Bank Digital Currency (CBDC) in a monetary model in which fundamental-based bank runs arise endogenously. We demonstrate that introducing a CBDC designed to replicate the properties of cash displaces physical cash and, when offered at a sufficiently attractive rate, can increase the likelihood of a bank run. In contrast, when the CBDC is designed to resemble bank deposits, cash, CBDC, and deposits can coexist as media of exchange, and a high CBDC rate can eliminate the risk of runs. We further characterize the optimal CBDC policy within this framework.
Keywords: E42; E58; G21; 330; monetary equilibrium; bank run; CBDC